Unraveling oxidative stress response in the cestode parasite Echinococcus granulosus - Cancela, Martín (Sci Rep, 2019)
Cystic hydatid disease (CHD) is a worldwide neglected zoonotic disease caused by Echinococcus granulosus. The parasite is well adapted to its host by producing protective molecules that modulate host immune response. An unexplored issue associated with the parasite’s persistence in its host is how the organism can survive the oxidative stress resulting from parasite endogenous metabolism and host defenses. Here, we used hydrogen peroxide (H(2)O(2)) to induce oxidative stress in E. granulosus protoescoleces (PSCs) to identify molecular pathways and antioxidant responses during H(2)O(2) exposure. Using proteomics, we identified 550 unique proteins; including 474 in H(2)O(2)-exposed PSCs (H-PSCs) samples and 515 in non-exposed PSCs (C-PSCs) samples. Larger amounts of antioxidant proteins, including GSTs and novel carbonyl detoxifying enzymes, such as aldo-keto reductase and carbonyl reductase, were detected after H(2)O(2) exposure. Increased concentrations of caspase-3 and cathepsin-D proteases and components of the 26S proteasome were also detected in H-PSCs. Reduction of lamin-B and other caspase-substrate, such as filamin, in H-PSCs suggested that molecular events related to early apoptosis were also induced. We present data that describe proteins expressed in response to oxidative stress in a metazoan parasite, including novel antioxidant enzymes and targets with potential application to treatment and prevention of CHD.